2015
DOI: 10.1159/000430400
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Androgen and Dietary Advanced Glycation End Products on Female Rat Liver

Abstract: Background/Aims: Advanced glycation end products (AGEs) have been related to a wide range of liver disorders including hyperandrogenic states such as the Polycystic Ovary Syndrome (PCOS). The aim of the present study is to evaluate the potential impact of dietary glycotoxins exposure and androgen excess on hepatic histology and biochemistry in an androgenized female rat model. Methods: The study population consisted of 80 female Wistar rats, divided in 3 groups, a group of prepubertal (Group A, n=30) and adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Higher level of insulin resistance and compensatory hyperinsulinaemia contribute to hyperandrogenism in PCOS and leads to the increase of T [35], arresting folliculogenesis through inhibition of granulosa cell proliferation and maturation, oestrogen and progesterone secretion and leading to anovulatory infertility [36]. A previous study on female rats revealed that androgen level may play an important role in liver metabolism and triglycerides level was also elevated in androgenized prepubertal rats compared to non-androgenized rats [37], which may provide a clue about the correlation between PCOS and obesity. In this study, we found that the basal levels of FSH and LH were significantly reduced in obese non-PCOS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Higher level of insulin resistance and compensatory hyperinsulinaemia contribute to hyperandrogenism in PCOS and leads to the increase of T [35], arresting folliculogenesis through inhibition of granulosa cell proliferation and maturation, oestrogen and progesterone secretion and leading to anovulatory infertility [36]. A previous study on female rats revealed that androgen level may play an important role in liver metabolism and triglycerides level was also elevated in androgenized prepubertal rats compared to non-androgenized rats [37], which may provide a clue about the correlation between PCOS and obesity. In this study, we found that the basal levels of FSH and LH were significantly reduced in obese non-PCOS patients.…”
Section: Discussionmentioning
confidence: 99%
“…The high levels of androgen and advanced glycation end products (AGEs) in PCOS women induces oxidative stress and inflammation [3]. Recent reports showed strong involvement of oxidative stress [4, 5] and endothelial dysfunction [6-8] in PCOS pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Jones et al compared several metabolic parameters in PCOS women with and without AE diagnosed according to the Rotterdam criteria and found that liver fat was significantly higher in hyperandrogenic PCOS compared to normoandrogenic PCOS women (diagnosed with PCOS due to PCO + AO), even after adjustment for obesity, IR and visceral and intra-abdominal fat (152). Androgenised female rats fed with a diet rich in advanced glycation end products have been shown to develop deranged hepatic function (153). However, putative causative mechanisms underlying PCOS-related NAFLD remain to be elucidated.…”
Section: Non-alcoholic Fatty Liver Disease (Nafld) and Male And Femalmentioning
confidence: 99%